Integrative flavoromics-GC-MS/IMS approach to study the formation mechanism of fishy flavor in skipjack tuna oil induced by oxidation and heat - Xianling Lan; Xiaoqin Pan; Jiawei Luo; Shan Xiao; Yanxue Cai; Jihui Wang (Food Chemistry: X)
Skipjack tuna oil that is rich in polyunsaturated fatty acids, is prone to developing fishy odors under high-temperature or oxidative conditions. This study investigated the effects of four treatments—low-temperature thermal, low-concentration oxidation, high-concentration oxidation, and high-temperature thermal—on oxidation degree, volatile compounds, fatty acids, and sensory characteristics. GC–MS identified five key volatile compounds: hexadecanoic acid, ethyl ester; octadecanoic acid, ethyl ester; ethyl oleate; ethyl 9-hexadecenoate; and ethyl 6,9,12,15-octadecatetraenoate. Oxidation induction significantly increased peroxide value and acid value, primarily by generating aldehydes (e.g., hexanal, heptanal), which intensified fishy odors. In contrast, by GC-IMS analysis, higher concentrations of fishy odor markers, 1-octen-3-ol (0.48 ± 0.05 %), 2-ethylfuran-D (0.75 ± 0.01 %), and (E)-2-heptenal-D (0.08 ± 0 %) were found in the high temperature thermal group, showing a more pronounced impact of thermal induction on flavor dynamics than oxidative pathways. These findings elucidate the dual roles of oxidation and thermal degradation in fishy odor formation.